Avaliação do estado emocional associado à catalepsia causada pela administração intraperitoneal de haloperidol - Colombo, Ana Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Haloperidol is a dopamine receptor antagonist used to treat schizophrenia. When systemically administered in rodents, haloperidol induces catalepsy, a state of immobility very similar to that seen in Parkinson's disease. It is known that many of Parkinson's disease symptoms are dependent on the emotional state since patients are still able to respond to external triggers such as loud noise or visual signaling. Recent data highlighted the importance of glutamatergic neurotransmission in the inferior colliculus (IC) on the cataleptic state induced by haloperidol in rats. Given the importance of IC in the brain aversion system and its connections to motor pathways, and based on the clinical reports of the emotional influence on the motor aspect of Parkinson's disease, the objective of the present study was to evaluate the emotional aspect related to catalepsy induced by intraperitoneal administration of haloperidol. To this end, we analysed ultrasonic vocalizations (UVs) of 22 kHz (indicative of aversion) in rats during the tests of catalepsy, open field and contextual conditioned fear. Systemic administration of haloperidol affected the motor activity, inducing catalepsy and decreasing exploratory activity in the open field. There were no UVs of 22 kHz resulting from treatment with haloperidol in catalepsy or open field tests. In the contextual conditioned fear test, haloperidol increased freezing when administered before the test, but decreased freezing on test day when administered before training. In this same test, haloperidol decreased the UVs on the day it was administered (training or test). The catalepsy induced by systemic administration of haloperidol seems to have also affected the motor aspect of UVs. In this way, it was not possible to clarify the existence of an aversive emotional state associated haloperidol induced catalepsy

O haloperidol é um antagonista de receptores dopaminérgicos utilizado no tratamento da esquizofrenia. Quando administrado de forma sistêmica em roedores, o haloperidol induz catalepsia, um estado de imobilidade muito semelhante ao observado na doença de Parkinson. Sabe-se que muitos dos sintomas do Parkinson são dependentes do estado emocional já que os pacientes imóveis são capazes de responder a gatilhos externos como barulho alto ou sinalização visual. Dados recentes destacam a importância da neurotransmissão glutamatérgica do colículo inferior (CI) sobre o estado cataléptico induzido pelo haloperidol em ratos. Tendo em vista a importância do CI no sistema aversivo e suas conexões com vias motoras, e conhecendo os relatos clínicos da influência emocional sobre o aspecto motor no Parkinson, pretendeu-se no presente estudo avaliar o estado emocional associado à catalepsia causada pela administração intraperitoneal de haloperidol. Para tanto, avaliamos a resposta defensiva dos animais por meio da análise das vocalizações ultrassônicas (VUs) de 22 kHz (indicativas de aversão) durante os testes de catalepsia, do campo aberto e do medo condicionado ao contexto. A administração sistêmica de haloperidol afetou a atividade motora em ratos, induzindo a catalepsia e diminuindo a atividade exploratória no campo aberto. Não foram observadas VUs de 22 kHz decorrentes do tratamento com haloperidol nos testes da catalepsia ou do campo aberto. No teste do medo condicionado ao contexto, o haloperidol aumentou o congelamento quando administrado antes do teste, mas diminuiu o congelamento no dia do teste quando administrado antes do treino. Nesse mesmo teste, o haloperidol diminuiu as VUs no dia em que foi administrado (treino ou teste). A catalepsia induzida pela administração sistêmica de haloperidol parece também ter afetado... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Neuropsicofarmacologia; Psicotropicos; Neurofarmacologia; Parkinson, Doença de; Saude mental